A parametric study of graphite dust deposition on high-temperature gas-cooled reactor (HTGR) steam generator tube bundles. (January 2019) - Wei, Mingzhe; Zhang, Yiyang; Wu, Xinxin; Sun, Libin
Abstract: Accumulation of abraded graphite dust is a major concern during a potential accident in high-temperature gas-cooled reactors (HTGR). AVR experiments indicated that it is of great safety interest to develop and benchmark numerical approaches for predicting deposition of dust particles in steam generator (SG) area. The present study analyzes the deposition behavior of graphite dust on one typical part of HTGR SG tube bundles using the open source CFD code OpenFOAM. The effects of Reynolds number, temperature difference and bundle structure parameters are discussed. The results show that the mechanism of thermophoresis dominates the deposition of particles below 2 μm, and the inertia impact becomes important for larger particles. As the flow Reynolds number increases, the impact rate decreases in the thermophoresis-controlled regime but increases in the inertial regime and the peak of deposition rate shifts to the smaller size. The effect of flow Reynolds number can be entirely represented by particle Stokes number in the inertia regime. As for the effect of bundle arrangement parameters, the impact rate first increases and then decreases as the longitudinal spacing increases, and decreases as the transverse spacing increases.